The theory of the legal entity in civil law: concept and value - Mulkubaeva, Sh.R.; Ilyassova, G.A. (KSU publ, 2015)
The problems of definition of concepts and construction of the legal entity, its signs, history of development of institute of the legal entity, formation of concept of the legal entity in historical aspect and value of the legal entity in modern civil legislation are considered in this article. The legal entities are formed in many spheres of public and economic activity. Authors, analyzing the concept and value of the legal entity, come to conclusion that the legal entity is independent and property isolated subject having the rights and duties, his founders, as a rule, don't answer on its debts.
Keywords: Civil law; legal entity; concept of legal entity; value of legal entity; historical aspect; founders